Implementasi Community Based Tourism (CBT) di Desa Wisata Tinalah Kabupaten Kulon Progo - Ummy Rofingatun Khasanah; S. Agus Santosa (Jurnal Mahasiswa Wacana Publik, 2022)
The purpose of this study is to determine the implementation of Community Based Tourism (CBT) in Tinalah Tourism Village. This research uses descriptive qualitative method with informant selection technique, namely purposive sampling. This study uses primary data was obtained through interviews and documentation, while secondary data was obtained from several previous studies through books, journals, and news. Data collection is done by direct technique which includes interviews and documentation. The data analysis technique in this study was adopted from Miles, Huberman and Saldana (2014) which was carried out through several stages, namely data collection, data reduction, data display, and conclusion drawing/verification. The theory used in this research is the implementation theory of Richard Matland. The results of this study indicate that the Community Based Tourism (CBT) policy in Tinalah Tourism Village is in accordance with applicable regulations and implemented by the competent authorities. However, not all of these communities have joined in the management of the Tinalah Tourism Village due to the lack of socialization and education about tourism villages, and not all communities can feel the impact.